Clopidogrel-Induced Recurrent Polyarthritis - Sahil Agrawal MD; Joseph Harburger MD; Gary Stallings MD, MPH; Nikhil Agrawal MD; Jalaj Garg MD (SAGE Publishing, 2013)
Clopidogrel is an oral thienopyridine and together with aspirin is a component of dual antiplatelet therapy for the prevention of stent thrombosis after intracoronary stent placement. The common adverse effects from its use are an increased risk of bleeding, neutropenia, and rash. Arthralgia and backache are also known to occur with its use. There have been case reports linking arthritis with the use of clopidogrel. We describe the case of a 64-year-old man who reported symptoms of fever and joint pains following initiation of therapy with clopidogrel. Acute-phase reactants were elevated. Laboratory and radiologic testing were unremarkable. Incidentally, he reported experiencing a similar arthritis after he received a loading dose of clopidogrel prior to a diagnostic coronary angiography in the past. The symptoms improved dramatically on discontinuation of clopidogrel. There was no recurrence of symptoms with prasugrel. This describes possibly the second incidence of recurrent arthritis with clopidogrel therapy.